PENGARUH HARGA TERHADAP MINAT BELI MINYAK GORENG CAMAR PADA MINIMARKET INDOMARET CABANG DIPONEGORO KOTA AMBON - Romaryo Parinussa; Andrie Christina Salhuteru; Victor. R. Pattipeilohy (P3M Politeknik Negeri Ambon, 2024)
The selling price of a product is important for sellers in influencing consumer behavior when shopping, because it can trigger buying interest. The current research aims to determine the effect of price on buying interest in seagull cooking oil at the Indomaret minimarket, Diponegoro branch, Ambon City. This research was carried out using a quantitative, explanatory approach, with data collection techniques using questionnaires measured using a Likert scale and involving 80 respondents. The sampling technique was carried out using a simple random sampling method and using simple regression analysis as a research data analysis technique. The research results show that there is a positive and significant influence between the price variable on consumer buying interest, or in other words, the more affordable the selling price, the more consumers' buying interest will increase when shopping for cooking oil. Keyword: Price 1; Buying Interest 2;